Two new species of the genus Epermenia Hübner, [1825] and some new distributional and taxonomic records (Lepidoptera: Epermeniidae) - Reinhard Gaedike (SHILAP)
Two new species are described and illustrated: Epermenia (Calotripis) similella Gaedike, sp. n. and Epermenia (Cataplectica) lusitanica Gaedike, sp. n. The lectotype of Epermenia (Calotripis) strictellus (Wocke, 1867) and Epermenia (Cataplectica) iniquellus (Wocke, 1867) is designated. The first records of thirteen species are established for different countries.